Recent Developments of Nanostructures for the Ocular Delivery of Natural Compounds - Razavi, Malihe Sadat; Ebrahimnejad, Pedram; Fatahi, Yousef; D’Emanuele, Antony; Dinarvand, Rassoul (Frontiers in Chemistry, 2022)
Ocular disorders comprising various diseases of the anterior and posterior segments are considered as the main reasons for blindness. Natural products have been identified as potential treatments for ocular diseases due to their anti-oxidative, antiangiogenic, and anti-inflammatory effects. Unfortunately, most of these beneficial compounds are characterised by low solubility which results in low bioavailability and rapid systemic clearance thus requiring frequent administration or requiring high doses, which hinders their therapeutic applications. Additionally, the therapeutic efficiency of ocular drug delivery as a popular route of drug administration for the treatment of ocular diseases is restricted by various anatomical and physiological barriers. Recently, nanotechnology-based strategies including polymeric nanoparticles, micelles, nanofibers, dendrimers, lipid nanoparticles, liposomes, and niosomes have emerged as promising approaches to overcome limitations and enhance ocular drug bioavailability by effective delivery to the target sites. This review provides an overview of nano-drug delivery systems of natural compounds such as thymoquinone, catechin, epigallocatechin gallate, curcumin, berberine, pilocarpine, genistein, resveratrol, quercetin, naringenin, lutein, kaempferol, baicalin, and tetrandrine for ocular applications. This approach involves increasing drug concentration in the carriers to enhance drug movement into and through the ocular barriers.